Dysprosium acetate solution method doped ZnO voltage-sensitive ceramic and preparation method thereof

Doping ZnO pressure-sensitive ceramics by dysprosium acetate solution method, and using Dy(C2H3O2)3·4H2O improvement process, the problem of insufficient voltage gradient and nonlinear coefficient of the existing ZnO resistor sheet is solved, and the preparation of high-performance ceramic materials is realized, with environmental protection and economic advantages.

CN119912253AActive Publication Date: 2025-05-02CHONGQING UNIV +3
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510002159.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-05-02
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The insufficient voltage gradient and nonlinear coefficient of the existing ZnO resistor chips limit their promotion and use in high-end applications, and the production process has environmental pollution problems.

Method used

ZnO pressure-sensitive ceramics are doped by dysprosium acetate solution method, and the composition and sintering process of the ceramics are optimized by adding Dy(C2H3O2)3·4H2O as a sintering additive and performance improver, and the voltage gradient and nonlinear coefficient are improved.

Benefits of technology

It realizes the ultra-high voltage gradient and nonlinear coefficient of ZnO voltage-sensitive ceramics, reduces leakage current density, simple process, small energy consumption, green and environmentally friendly, practical and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912253A_ABST
    Figure CN119912253A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrahigh voltage gradient and nonlinear coefficient dysprosium acetate solution method doped ZnO voltage-sensitive ceramic and a preparation method, the ZnO voltage-sensitive ceramic is composed of ZnO, a voltage-sensitive forming agent Bi2O3 and voltage-sensitive enhancers CoO, Mn2O3, Cr2O3, SnO2, CaO and Dy (C2H3O2) 3.4 H2O, the content of ZnO is 95.15-96.04 mol%, the content of the voltage-sensitive forming agent Bi2O3 is 1.0 mol%, the content of the voltage-sensitive enhancers Co3O4, MnO2, Cr2O3, SnO2 and CaO is 0.5 mol%, 0.5 mol%, 0.5 mol%, 1.0 mol% and 0.45 mol% respectively, and the content of Dy (C2H3O2) 3.4 H2O is 0.01-0.9 mol%. According to the invention, Dy (C2H3O2) 3.4 H2O is not only a modifier but also a sintering aid. The invention also provides a preparation method of the ZnO voltage-sensitive ceramic with ultrahigh voltage gradient and nonlinear coefficient. The problems that an existing high-voltage voltage-sensitive ceramic preparation method is difficult, and the obtained high-voltage voltage-sensitive ceramic is poor in performance are solved, and meanwhile the preparation method has the advantages of being simple in process, small in energy consumption, environmentally friendly and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic production, and particularly relates to an ultra-high voltage gradient and nonlinear coefficient ZnO varistor ceramic and a preparation method thereof. Background Art

[0002] Pure ZnO ceramics do not have nonlinear characteristics and need to be doped with an appropriate amount of varistor forming agent (mainly Bi2O3, Pr6O 11 and V2O5) and varistor enhancers (mainly oxides such as Co2O3, Mn2O3, SnO2, Cr2O3, etc.) can show excellent nonlinear electrical characteristics on a macro scale. For this reason, ZnO varistor ceramics have become an ideal choice for limiting overvoltage in power systems due to their high nonlinear coefficient, excellent energy tolerance and low raw material cost. They are widely used in AC and DC lines and power equipment to effectively suppress transient voltages and absorb surges, while protecting sensitive electronic equipment from voltage fluctuations or mutations.

[0003] It is reported that Toshiba of Japan has successfully commercialized a high voltage gradient ZnO ceramic resistor with a voltage gradient of up to 1000V / mm and a leakage current as low as 3μA or less. The application of this resistor in 500kV gas insulated switchgear (GIS) arresters has shown significant advantages. Compared with the same type of arrester with a traditional voltage gradient of 600V / mm, the volume of the arrester using this high voltage gradient ZnO resistor has been reduced by 55%, and the manufacturing cost has been reduced by more than 30%. This technological advancement not only improves the performance of the arrester, but also significantly reduces the production cost, making high-voltage arresters more economical in large-scale applications. In contrast, the voltage gradient of the existing domestic mass-produced ZnO resistors is usually less than 400V / mm, the nonlinear coefficient is less than 60, and the leakage current is less than 20μA. Although these resistors can meet the basic needs of domestic ultra-high voltage AC and DC arresters, there is still a clear gap in technical level compared with the international advanced level. This not only affects the performance of the arrester, but also limits its promotion and use in high-end application fields.

[0004] Explore new processes and material systems to reduce the impact of production on the environment and promote the development of lightning arresters in terms of safety, performance, miniaturization and green manufacturing. Improving the performance of ZnO varistors and optimizing their preparation processes are key, which not only improves the performance of lightning arresters, but also promotes green manufacturing and reduces environmental pollution. Summary of the invention

[0005] In view of the above problems existing in the prior art, the purpose of the present invention is to develop a dysprosium acetate solution-doped ZnO varistor ceramic with ultra-high voltage gradient and nonlinear coefficient.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solution: a ZnO varistor ceramic doped with dysprosium acetate solution method, characterized in that the composition expression of the ZnO varistor ceramic is:

[0007] (100-x)mol%ZnO+1.0mol%Bi2O3+0.5mol%Co3O4+0.5mol%MnO2+0.5mol%Cr2O3+1.0mol%SnO2

[0008] +0.45mol%CaO+xmol%Dy(C2H3O2)3·4H2O, where 0.01≤x≤0.9. The Dy(C2H3O2)3·4H2O can be used to improve the high voltage gradient and nonlinear coefficient of the varistor ceramic, and can also be used as a sintering aid to assist the densification process. The voltage gradient E of the high voltage gradient and nonlinear coefficient ZnO varistor ceramic b The nonlinear coefficient α is 1364~5431V / mm, the maximum value is 142.16, and the leakage current density I L Minimum 0.07μA / cm 2 The modifying additives include: 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, 0.45 mol% CaO and (0.01-0.9) mol% Dy(C2H3O2)3·4H2O.

[0009] A method for preparing ZnO varistor ceramics doped with dysprosium acetate solution comprises the following steps:

[0010] S1: Weigh the original powders of ZnO, Bi2O3, Co3O4, MnO2, Cr2O3, SnO2 and CaO according to the above-defined stoichiometric ratio, put them into a ball mill and mix them thoroughly with anhydrous ethanol zirconium balls, take out the mixed powder, dry it, sieve it with a 60-mesh screen and set it aside. Ball mill at a speed of 380r / min for 12h, dry it in an oven at 80℃, and dry it for at least 12h.

[0011] S2: Weigh the original powder of Dy(C2H3O2)3·4H2O according to the above stoichiometric ratio and dissolve it in the polar aqueous solution to obtain a mixed solution for use; the Dy element is doped into the varistor through the polar aqueous solution, which plays a role in dissolving Dy(C2H3O 2)3 ·4H2O, and also plays a role in making the Dy element uniformly distributed in the ZnO matrix. 2)3 4H2O can be used as a sintering aid to assist the densification process.

[0012] S3: Mix the mixed powder in S1 and the mixed solution in S2 evenly in a mortar. The amount of the mixed solution added is 10-40wt% of the mixed powder. After the mixed powder is fully moistened, the mixed powder is placed in a mold and pressurized at 200-500MPa. At the same time, it is heated to 200-400℃ and kept warm for 30min-2h to obtain a preliminary densified ZnO varistor ceramic embryo.

[0013] S4: The ZnO varistor ceramic body in S3 is placed in a muffle furnace and sintered at a sintering temperature of 700-1000°C for 1-5 hours to further densify the ZnO varistor ceramic body to obtain a ZnO varistor ceramic product. The sintering temperature of the varistor in S4 only needs to be 700-1000°C, which is much lower than the sintering temperature of the commercial method.

[0014] Furthermore, the mass ratio of the powder, zirconium balls and ball milling liquid medium in S1 is 1:10:1.5, wherein the mass ratio of the zirconium balls with a diameter of 1 cm, a diameter of 0.5 cm and a diameter of 0.2 cm is 2:1:1, and the speed of the high-energy ball mill is 380 r / min.

[0015] Furthermore, the particle size of the original ZnO powder in the S1 is ~500nm, and the particle sizes of the original Bi2O3, Co3O4, MnO2, Cr2O3, SnO2 and CaO powders are ~100nm, ~200nm, 100~300nm, ~200nm, <250nm and <160nm, respectively.

[0016] Furthermore, the relative density of the ZnO varistor ceramic body in S3 is 88%-94%.

[0017] Furthermore, the sintering heating rate in S4 is 0.5-2°C / min. Since the original embryo prepared in S3 has a high initial density and the internal stress of the embryo is large, a high heating rate can easily cause the sample to crack. Therefore, the heating rate in S4 is selected to be less than or equal to 2°C / min, which helps the sample to slowly release internal stress during further densification.

[0018] Compared with the prior art, the beneficial effects of the present invention are:

[0019] 1. Compared with the traditional sintering method, the present invention has made innovations in the sintering process. The added Dy(C2H3O2)3·4H2O sintering aid makes the ZnO varistor ceramics initially densified at 300°C and 300MPa pressure, and finally further densified at a sintering temperature of 700-1000°C. During the initial densification, the low sintering temperature of the water molecules and some acetate ions in Dy(C2H3O2)3·4H2O controls the varistor ceramic grains within the micro-nano range, which helps to improve the voltage gradient of the varistor ceramics.

[0020] 2. In the present invention, Dy(C2H3O2)3·4H2O is used as an auxiliary sintering agent to promote initial densification. During the heating process, Dy(C2H3O2)3·4H2O first loses its crystal water between 100-200°C, which promotes the material transfer during the sintering process. Then, the acetate ions are decomposed into water and carbon dioxide at above 200°C, which further promotes the plastic deformation during the sintering process.

[0021] 3. In the present invention, Dy(C2H3O2)3·4H2O is not only a sintering aid, but also a performance improver. The present invention prepares a ZnO varistor ceramic material with excellent varistor properties by doping Dy(C2H3O2)3·4H2O. With the increase of the doping amount of Dy(C2H3O2)3·4H2O, its potential gradient shows a trend of increasing continuously, and the nonlinear coefficient shows a trend of increasing first and then decreasing. When the doping amount of Dy(C2H3O2)3·4H2O is 0.5mol%, the performance is the best, and the voltage gradient is E b is 2564.37V / mm, the nonlinear coefficient α is up to 142.16, and the leakage current density I L Minimum 0.07μA / cm 2 In addition, the preparation method of the present invention has the advantages of simple process, low energy consumption, green environmental protection, etc., and has practicality and application prospects.

[0022] 4. The addition of Dy element can effectively improve the performance of ZnO varistor ceramics. ZnO varistor ceramics are widely used in circuit protection, overvoltage protection and other fields, and their performance is affected by factors such as material composition and microstructure. The incorporation of Dy element can have a significant effect on the electrical properties, structural stability and varistor effect of ZnO. The specific improvement mechanism can be analyzed from the following aspects: ① Improve the crystal structure of ZnO: As a rare earth element, Dy element has a large ion radius, which can effectively improve the lattice defects of ZnO and promote the uniform growth of grains, thereby improving the crystal quality of ZnO. The incorporation of Dy element helps to reduce oxygen vacancies and defects in ZnO and enhance the structural stability of the material. Dy element may replace zinc (Zn) ions into the ZnO lattice to form a solid solution, thereby changing the microstructure of ZnO and further improving the electrical conductivity and varistor properties of the material. ② Adjust the electronic structure and band structure: The incorporation of Dy can affect the band structure of ZnO, especially the adjustment of the band gap. The d orbital electrons of the Dy element can interact with the conduction band of ZnO, which may cause the mobility of the electrons in the conduction band of ZnO to change, thereby optimizing the electrical properties of the material. This can improve the response speed and sensitivity of ZnO varistor ceramics to a certain extent. By adjusting the band structure, the Dy element can improve the electronic conductivity of ZnO, especially under low voltage or high voltage difference conditions, which can effectively reduce the switching voltage of ZnO varistor ceramics and enhance its stability. ③ Improve the interface state and conductivity characteristics: The Dy element can change the interface state between ZnO particles, enhance the connection between particles, optimize the flow path of electrons, reduce the scattering of electrons, and improve the conductivity. The incorporation of the Dy element helps to form an electronic state that is conducive to conductivity, which greatly improves the electrical properties of ZnO varistor ceramics (such as nonlinear index and varistor coefficient). ④ Enhance the varistor effect of the material: In ZnO-based varistor ceramic materials, the varistor effect is determined by the relationship between the conductivity of the material and the applied voltage. After the addition of Dy, the nonlinear conductivity and nonlinear coefficient of ZnO are usually improved, making the varistor effect of the material more significant. The addition of Dy can increase the energy band gap of ZnO and reduce the excitation energy of current under high voltage, thereby enhancing the varistor of ZnO and providing stronger voltage response capability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the relative density of ZnO varistor ceramics sintered at different sintering temperatures.

[0024] Figure 2 The voltage gradient of ZnO varistor ceramics doped with different Dy(C2H3O2)3·4H2O contents.

[0025] Figure 3 is the nonlinear coefficient of ZnO varistor ceramics doped with different Dy(C2H3O2)3·4H2O contents. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention.

[0027] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can understand other advantages and effects of the present invention from the contents of the present invention. The present invention can also be applied through different embodiments, and the details in this specification can also be modified or adjusted according to different viewpoints and applications without changing the basic spirit of the present invention.

[0028] Please note that the process equipment or devices not specifically described in the following embodiments are all conventional equipment or devices in the art. All pressure values ​​and ranges refer to relative pressures, and the raw materials used are also materials conventionally used in the art.

[0029] Embodiment 1:

[0030] (1) weighing 96.04 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0031] (2) weighing 0.01 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0032] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 40 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, a uniaxial pressure of 500 MPa is applied by a manual tablet press, and a temperature of 400° C. is applied to the mold by a heating sleeve. After keeping the temperature for 30 min, a preliminarily densified ZnO varistor ceramic is obtained;

[0033] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 850° C. for 3 h at a heating rate of 2° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0034] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 98.61% and has excellent electrical properties, voltage gradient Eb is 1844.63V / mm, the nonlinear coefficient α is 54.33, and the leakage current density I L 0.25μA / cm 2 .

[0035] Embodiment 2:

[0036] (1) weighing 95.95 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0037] (2) weighing 0.1 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0038] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 35 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, a uniaxial pressure of 400 MPa is applied by a manual tablet press, and a temperature of 400° C. is applied to the mold by a heating sleeve. After keeping the temperature for 1 h, a preliminarily densified ZnO varistor ceramic is obtained;

[0039] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 850° C. for 3 h at a heating rate of 2° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0040] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 98.58% and has excellent electrical properties, voltage gradient E b is 2059.11V / mm, the nonlinear coefficient α is 63.19, and the leakage current density I L 0.28μA / cm 2 .

[0041] Embodiment 3:

[0042] (1) weighing 95.75 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0043] (2) weighing 0.3 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0044] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 30 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, a uniaxial pressure of 400 MPa is applied by a manual tablet press, and a temperature of 300° C. is applied to the mold by a heating sleeve. After keeping the temperature for 30 min, a preliminarily densified ZnO varistor ceramic is obtained;

[0045] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 850° C. for 3 h at a heating rate of 1° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0046] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 98.53% and has excellent electrical properties, voltage gradient E b is 2338.84V / mm, the nonlinear coefficient α is 88.94, and the leakage current density I L 0.11μA / cm 2 .

[0047] Embodiment 4:

[0048] (1) weighing 95.55 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0049] (2) weighing 0.5 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0050] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 25 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, a uniaxial pressure of 300 MPa is applied by a manual tablet press, and a temperature of 300° C. is applied to the mold by a heating sleeve. After keeping the temperature for 1 h, a preliminarily densified ZnO varistor ceramic is obtained;

[0051] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 850° C. for 3 h at a heating rate of 1° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0052] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 98.36% and has excellent electrical properties, voltage gradient E b is 2564.37V / mm, the nonlinear coefficient α is 142.16, and the leakage current density I L 0.07μA / cm 2 .

[0053] Embodiment 5:

[0054] (1) weighing 95.35 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0055] (2) weighing 0.7 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0056] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 20 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, a uniaxial pressure of 300 MPa is applied by a manual tablet press, and a temperature of 200° C. is applied to the mold by a heating sleeve. After keeping the temperature for 1.5 h, a preliminarily densified ZnO varistor ceramic is obtained;

[0057] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 850° C. for 3 h at a heating rate of 0.5° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0058] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 98.21% and has excellent electrical properties, voltage gradient E b is 2632.33 V / mm, the nonlinear coefficient α is 95.51, and the leakage current density I L 0.12μA / cm 2 .

[0059] Embodiment 6:

[0060] (1) weighing 95.15 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0061] (2) weighing 0.9 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0062] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 10 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, and a uniaxial pressure of 200 MPa is applied by a manual tablet press, and a temperature of 200° C. is applied to the mold by a heating sleeve. After keeping the temperature for 2 h, a preliminarily densified ZnO varistor ceramic is obtained;

[0063] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 850° C. for 3 h at a heating rate of 0.5° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0064] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 98.32% and has excellent electrical properties, voltage gradient E b is 2718.69V / mm, the nonlinear coefficient α is 76.52, and the leakage current density I L 0.72μA / cm 2 .

[0065] Embodiment 7:

[0066] (1) weighing 95.55 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0067] (2) weighing 0.5 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0068] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 25 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, and a uniaxial pressure of 300 MPa is applied by a manual tablet press, and a temperature of 300° C. is applied to the mold by a heating sleeve. After keeping the temperature for 30 min, a preliminarily densified ZnO varistor ceramic is obtained;

[0069] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 700° C. for 5 h at a heating rate of 1° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0070] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 93.07% and has excellent electrical properties, voltage gradient E b is 5431.66V / mm, the nonlinear coefficient α is 14.37, and the leakage current density I L 17.66μA / cm 2 .

[0071] Embodiment 8:

[0072] (1) weighing 95.55 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0073] (2) weighing 0.5 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0074] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 25 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, a uniaxial pressure of 300 MPa is applied by a manual tablet press, and a temperature of 300° C. is applied to the mold by a heating sleeve. After keeping the temperature for 1 h, a preliminarily densified ZnO varistor ceramic is obtained;

[0075] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 775° C. for 4 h at a heating rate of 1° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0076] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 96.17% and has excellent electrical properties, voltage gradient E b is 4025.61V / mm, the nonlinear coefficient α is 49.21, and the leakage current density I L 5.87μA / cm 2 .

[0077] Embodiment 9:

[0078] (1) weighing 95.55 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0079] (2) weighing 0.5 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0080] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 25 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, and a uniaxial pressure of 300 MPa is applied by a manual tablet press, and a temperature of 300° C. is applied to the mold by a heating sleeve. After keeping the temperature for 1.5 h, a preliminarily densified ZnO varistor ceramic is obtained;

[0081] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 925° C. for 2 h at a heating rate of 0.5° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0082] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 98.25% and has excellent electrical properties, voltage gradient E b is 1942.47V / mm, the nonlinear coefficient α is 78.17, and the leakage current density I L 0.27μA / cm 2 .

[0083] Embodiment 10:

[0084] (1) weighing 95.55 mol% ZnO, 1.0 mol% Bi2O3, 0.5 mol% Co3O4, 0.5 mol% MnO2, 0.5 mol% Cr2O3, 1.0 mol% SnO2, and 0.45 mol% CaO raw powders according to the stoichiometric ratio and putting them into a ball mill, using anhydrous ethanol zirconium ball as the medium, and ball milling at a speed of 380 r / min for 12 h, then taking out the mixed powder and drying it in an oven at 80°C, and finally sieving it with a 60-mesh sieve for later use;

[0085] (2) weighing 0.5 mol% Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio and dissolving it in a polar aqueous solution to obtain a mixed solution for use;

[0086] (3) Weigh an appropriate amount of the powder in (1) and the mixed solution in (2), wherein the amount of the mixed solution is 25 wt % of the powder, and mix the two evenly in a mortar. After the powder is fully moistened, the powder is transferred into a ceramic mold, and a uniaxial pressure of 300 MPa is applied by a manual tablet press, and a temperature of 300° C. is applied to the mold by a heating sleeve. After keeping the temperature for 2 h, a preliminarily densified ZnO varistor ceramic is obtained;

[0087] (4) The ceramic green body in (3) is placed in a muffle furnace and sintered at a sintering temperature of 1000° C. for 1 h at a heating rate of 0.5° C. / min to further densify the green body to obtain a ZnO varistor ceramic product.

[0088] (5) Through relevant tests on the ZnO varistor ceramic product in (4), the final product can reach a relative density of 98.14% and has excellent electrical properties, voltage gradient E b is 1364.58V / mm, the nonlinear coefficient α is 56.39, and the leakage current density I L 1.83μA / cm 2 .

[0089] The performance tests were performed on the ZnO varistor ceramic samples obtained in Examples 1 to 24:

[0090] Table 1 Related parameters of ZnO varistor ceramics under different conditions

[0091]

[0092]

[0093] Through the above experimental results in the present invention, we can find the following experimental rules:

[0094] 1. The doping of Dy element in the present invention has a great influence on the key performance parameters of ZnO varistor ceramics. When the doping content is low, it can optimize the crystal structure of ZnO, improve the conductivity, and enhance the varistor characteristics; when the doping content is too high, it will lead to increased crystal defects, enhanced electron scattering, and weakened varistor characteristics.

[0095] 2. The appropriate sintering temperature is also crucial in the present invention. When the sintering temperature is too low, although an ultra-high potential gradient can be obtained, the low nonlinear coefficient and high leakage current density cannot meet commercial needs. This may be due to insufficient grain growth caused by the low sintering temperature, insufficient diffusion between particles, and the inability to effectively combine the grains. The formed ceramic body may have gaps or holes, affecting the density of the material; when the sintering temperature is too high, the varistor characteristics of the varistor ceramic are reduced mainly due to excessive sintering of particles, grain growth, oxidation or chemical reaction, melting or degradation of materials, porosity and density problems, thermal stress, etc. In order to ensure the good performance of the varistor ceramic, it is necessary to sinter at a suitable sintering temperature and environment to keep its electrical properties meeting the requirements.

Claims

1. A ZnO varistor ceramic doped with dysprosium acetate solution, characterized in that: The composition expression of the ZnO varistor ceramic is: (100-x) mol% ZnO+1.0mol% Bi2O3+0.5mol% Co3O4+0.5mol% MnO2+0.5mol% Cr2O3+1.0mol% SnO2+0.45mol% CaO+xmol% Dy(C2H3O2)3·4H2O, wherein 0.01≤x≤0.

9.

2. A method for preparing ZnO varistor ceramics doped with dysprosium acetate solution, characterized in that: The steps include: S1: weigh ZnO, Bi2O3, Co3O4, MnO2, Cr2O3, SnO2, and CaO raw powders according to the stoichiometric ratio defined in claim 1, put them into a ball mill, use anhydrous ethanol zirconium ball as a medium, and mix them thoroughly by ball milling. Then, take out the mixed powder, dry it, and sieve it with a 60-mesh sieve for later use; S2: weighing Dy(C2H3O2)3·4H2O original powder according to the stoichiometric ratio defined in claim 1, and dissolving it in a polar aqueous solution to obtain a mixed solution for later use; S3: The mixed powder in S1 and the mixed solution in S2 are mixed evenly in a mortar, wherein the amount of the mixed solution added is 10-40wt% of the mixed powder, and after the mixed powder is fully moistened, the mixed powder is placed in a mold, and a pressure of 200-500MPa is applied, and the mixed powder is heated to 200-400°C and kept warm for 30min-2h to obtain a preliminarily densified ZnO varistor ceramic embryo; S4: placing the ZnO varistor ceramic body in S3 into a muffle furnace, and sintering it at a sintering temperature of 700-1000° C. for 1-5 hours to further densify the ZnO varistor ceramic body to obtain a ZnO varistor ceramic product.

3. The method for preparing ZnO varistor ceramics doped with dysprosium acetate solution as claimed in claim 2, characterized in that: The mass ratio of the powder, zirconium balls and ball milling liquid medium in S1 is 1:10:1.5, wherein the mass ratio of the zirconium balls is 2:1:1 for diameters of 1 cm, 0.5 cm and 0.2 cm, and the rotation speed of the high-energy ball mill is 380 r / min.

4. The method for preparing ZnO varistor ceramics doped with dysprosium acetate solution as claimed in claim 2, characterized in that: The particle size of the original ZnO powder in the S1 is ~500nm, and the particle sizes of the original Bi2O3, Co3O4, MnO2, Cr2O3, SnO2 and CaO powders are ~100nm, ~200nm, 100~300nm, ~200nm, <250nm and <160nm respectively.

5. The method for preparing ZnO varistor ceramics doped with dysprosium acetate solution as claimed in claim 2, characterized in that: The relative density of the ZnO varistor ceramic body in S3 is 88%-94%.

6. The method for preparing ZnO varistor ceramics doped with dysprosium acetate solution as claimed in claim 2, characterized in that: The heating rate of the sintering in S4 is 0.5-2°C / min.

Citation Information

Patent Citations

  • Rare earth nitrate doping zinc oxide pressure-sensitive ceramic material and preparation method thereof

    CN101265083A

  • Ultrahigh-gradient zinc oxide piezoresistor and preparation method thereof

    CN106278239A

  • Preparation method of high-voltage-gradient ZnO voltage-sensitive microspheres

    CN106966716A

  • Ultrahigh-potential-gradient ZnO voltage-sensitive ceramic and low-carbon sintering preparation process thereof

    CN115385682A

  • AU2020102274A4